A New Trait in the Biography of Kalokyros from Cherson - Nikolay Alekseienko; Aleksey Arzhanov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The limited range of written sources, studied to a certain extent that provided various interpretations of the Byzantine prosopography, makes every new monument of sigillography capable of replenishing and enlarging our notion of this or that historical figure (by clarifying their careers or biographies) a very valuable source, sometimes allowing the one to enlarge the earlier known account. This is certainly the case of the seals of the famous Kalokyros, a member of the elite of Cherson. Methods. The comparative analysis of the written sources account and the earlier-known molybdoboulla of this member of the administration of Cherson uncovers some of the pages (still rather disputably) of his biography and career. All the rest is still a matter of discussion. Analysis and results. In this connection, one of the new sigillographic finds in Cherson is of particular interest, as it reveals a previously unknown episode from the life of this representative of the local elite. The seal legend states that its owner, Kalokyros by name, possessed the rank of protospatharios and held the position of the proteuon of Cherson. There is no doubt that the new seal reflects the earliest stage of his career, before he got the title of patrikios and took part in the well-known Byzantine embassy to Prince Sviatoslav of Rus’ (in 967 AD), and, accordingly, clarifies the Byzantine written sources’ account on the status of this representative of Cherson. Contribution of authors: Нistorical, sigillographic and epigraphic analysis – N.A. Alekseienko; historical and archaeological survey – A.Yu. Arzhanov.